Coffee intake and decreased amyloid pathology in human brain - Kim, Jee Wook (Transl Psychiatry, 2019)
Several epidemiological and preclinical studies supported the protective effect of coffee on Alzheimer’s disease (AD). However, it is still unknown whether coffee is specifically related with reduced brain AD pathologies in human. Hence, this study aims to investigate relationships between coffee intake and in vivo AD pathologies, including cerebral beta-amyloid (Aβ) deposition, the neurodegeneration of AD-signature regions, and cerebral white matter hyperintensities (WMH). A total of 411 non-demented older adults were included. Participants underwent comprehensive clinical assessment and multimodal neuroimaging including [(11)C] Pittsburgh compound B-positron emission tomography (PET), [(18)F] fluorodeoxyglucose PET, and magnetic resonance imaging scans. Lifetime and current coffee intake were categorized as follows: no coffee or <2 cups/day (reference category) and ≥2 cups/day (higher coffee intake). Lifetime coffee intake of ≥2 cups/day was significantly associated with a lower Aβ positivity compared to coffee intake of <2 cups/day, even after controlling for potential confounders. In contrast, neither lifetime nor current coffee intake was not related to hypometabolism, atrophy of AD-signature region, and WMH volume. The findings suggest that higher lifetime coffee intake may contribute to lowering the risk of AD or related cognitive decline by reducing pathological cerebral amyloid deposition.